Navigation and Waterpower : Adaptation and Technology on Canadian Canals - Desjardins, Pauline (The Journal of the Society for Industrial Archeology, 2003)
Keywords: Navigation; Énergie hydraulique

Steamboat connections : Montreal to Upper Canada, 1816-1843 - Mackey, Frank (McGill-Queen's University Press, 2000)
"In Steamboat Connections Frank Mackey gives us a narrative account of the first twenty-five years of steam navigation along the St. Lawrence and Ottawa Rivers. Relying on a wealth of primary archival sources, Mackey focuses on the development of steamer traffic from 1816 - when the foundations were laid for the first stage and steamboat line between Montreal and Upper Canada - to the early 1840s - when locks, canals, innovations, and human daring conquered the rapids on those rivers and allowed for navigation between Montreal and the Great Lakes. He shows how, starting in 1841, small steamers ran "the circuit" - down the rapids of the St. Lawrence to Montreal and then back up to Kingston and other Great Lakes ports via the Ottawa River and the Rideau Canal." "Mackey introduces the entrepreneurs who forged this important link between Montreal and the nation's interior and chronicles the course of their industry, correcting previous misinterpretations. He sheds light not only on steamboats but also on the social, commercial, and geographical development they made possible. He shows that the history of this country, a land with vast expanses and a harsh climate, cannot be fully appreciated without looking at the different modes of transportation that made it possible."--BOOK JACKET.
Keywords: Navigation

La "Normandie du Nouveau Monde": la société Canada Steamship Lines, l’antimodernisme et la promotion du Québec ancien - Murton, James (Revue d'histoire de l'Amérique française, 2001)
Cette étude tend à montrer que durant les années 1930 la Canada Steamship Lines (CSL) a créé et disséminé une image du Québec comme société simple, prémoderne et rurale, dans le but d’accroître la clientèle de ses navires de croisière et de ses hôtels. On y examine les documents publicitaires de la compagnie et l’on montre qu’elle faisait aussi appel à d’autres individus pour construire cette image. L’anthropologue et folkloriste Marius Barbeau a écrit un ouvrage pour le compte de la CSL et celle-ci s’est associée au gouvernement du Québec pour promouvoir le renouveau artisanal. Ces divers acteurs partageaient la croyance antimoderne dans l’existence d’un Québécois vrai, authentique et qui constituait le coeur même de la nation : l’« Habitant ».
Keywords: Navigation

Le Saint-Laurent, comme une rue principale - Franck, Alain (Continuité, 2001)
Keywords: Navigation; Voie maritime

La rivière des Prairies - Dupont, Antonin (Il était une fois... Montréal-Nord, 2002)
Keywords: Navigation; Rivière des Prairies

La compagnie maritime Allan: de l'Écosse au Canada au XIXe siècle - Blondel-Loisel, Annie (Là-bas, 2009)
Keywords: Allan Royal Mail Line; Allan, Andrew; Allan, Hugh; Navigation

Voies pointelières d'hier et d'aujourd'hui - Desjardins, Pierre (Atelier d'histoire de Pointe-aux-Trembles, 2006)
Keywords: Chemins de fer; Navigation; Pointe-aux-Trembles; Quartiers

Transportons-nous, jadis! Une petite histoire du transport (Les Argoulets: bulletin de la Société d'histoire et de généalogie de Verdun, 2006)
Keywords: Automobile; Lachine (canal); Navigation; Ponts; Tramways; Transport en commun